MODELLING THE EFFECT OF VIBRATION ON THE SOUND ABSORPTION PERFORMANCE OF GREEN SOUND ABSORBER USING WAVE PROPAGATION TECHNIQUE - Putra, Azma; Sajidin, Muhammad; Salleh, Norliana; Hady, Efendy (Universiti Teknikal Malaysia Melaka, 2012)
Natural fibers (NF) have been known to have good acoustic performance and can potentially substitute the classical synthetic absorber materials which give negative impact for the environment. Commonly, the sound absorption model available for porous acoustic panel ignores the vibration of the panel. In this paper, the effect of the vibration on the sound absorption of the NF panel backed with a solid panel and air layer is modeled using wave propagation method. It is shown that the model can be adjusted into the case of an absorber panel backed with air layer and rigid surface by increasing the impedance of the solid panel.